PERSPEKTIF HUKUM ISLAM TERHADAP PENCALONAN DIRI DAN KAMPANYE UNTUK JABATAN POLITIK - Ashsubli, Muhammad (Faculty of Shariah of State Institute for Islamic Studies Batusangkar, Indonesia, 2016)
Self candidacy and campaign for particular political position by someone can be accepted in Islamic laws as long as he fulfills two important points. First, he or she possesses capacity, capability, and acceptability to assume positions he or she applying and campaigning for. Second, his or her genuine motivation is to seek for God’s willing and to realize public’s own good sake as well instead of striving for his or her own personal goals and medium for for things that are destructive for public needs.